Analysis of Financial Performance Before and After the Covid Pandemic : (Case Study on the Oil Palm Plantation Industry Listed on the Indonesia Stock Exchange) - Dian Novita Bukit; Irni Yunita (Publikasi Indonesia, 2025)
This research aims to examine trends and differences in the financial performance of palm oil companies listed on the Indonesia Stock Exchange, using Current Ratio, Quick Ratio, Debt to Asset Ratio, Debt to Equity Ratio, Net Profit Margin, Gross Profit Margin, Operating Profit Margin, Return on Assets, Return on Equity, Total Asset Turnover, and EBITDA Margin before, during, and after the COVID-19 pandemic. The research employs a descriptive analysis with a quantitative approach. The sample selection utilized a purposive sampling method, and the analytical methods include financial ratio analysis, trend analysis, and mean difference analysis (Paired Sample t-test). The findings reveal significant differences in financial performance before and after the pandemic, particularly in CR, QR, NPM, GPM, OPM, ROA, and ROE ratios based on formula calculations. However, statistical testing using IBM SPSS 26 indicated no significant differences across all financial ratio indicators.